MARITAL ROLE ADJUSTMENT AND SATISFACTION AMONG IGBO MARRIED WORKERS IN MBAITOLI LOCAL GOVERNMENT AREA OF IMO STATE, SOUTH EAST NIGERIA - Melvina N. Amalu; Nneka Sophie Amalu; Margaret E. Oyo-Ita (Universitas PGRI Madiun, 2022)
The purpose of the study was to examine the relationship between marital role adjustment and satisfaction among Igbo married workers in Mbaitoli Local Government Area of Imo State, Nigeria. Two hypotheses were formulated to direct the study and the correlational research design method was adopted. Simple random sampling technique was employed in selecting the sample of 170( 85 males and 85 females) out of one thousand, seven hundred Igbo married workers (1700). Data collection was with the aid of a questionnaire titled “Marital Role Expectation Inventory (MREI) and were analysed using Pearson Product Moment Corelation (PPMC). The reliability coefficient with split-half ranged from 0 .68 to 0.74. Findings revealed that a significantly positive but weak relationship existed between domestic role adjustment and marital satisfaction (r = 0.255; p = 0.001, SD 3.03). The relationship between financial role adjustment and marital satisfaction was found to be significantly positive and moderate (r = 0.472; p = 0.000, SD 2.48). Consequently, domestic and financial role adjustments can be said to have significant influence on marital satisfaction of Igbo married workers. It is recommended among others that the marriage counsellors in both private sectors should organize regular seminars, symposia, awareness programmes geared towards assisting married workers to acquire good marriage skills, through the introduction of good marriage therapies.